Minimally Invasive Coloproctology Advances in Techniques and Technology - Meng, William C S.; Cheung, Hester Y S.; Lam, David T Y.; Ng, Simon S M. (Springer International Publishing : Imprint: Springer, 2015)
In this book, pioneers and distinguished masters of surgery describe novel minimally invasive colo- and anorectal procedures that have been developed in Asia but are of international applicability. The presented techniques are wide ranging in nature and relate to colon surgery, rectal surgery, and the treatment of hemorrhoids, fistulas, and chronic constipation. Each procedure is carefully described with the aid of high-quality color photographs and illustrations, drawing attention to many practical tips and tricks. In addition to the techniques themselves, state of the art technology is introduced that is now being applied clinically in China, Hong Kong, Asia-Pacific, and beyond. The book will enable readers both to grasp the concepts underlying these important new approaches and advances and to reproduce the techniques in their own surgical practice.